Urban ecology studies of the amphibians and reptiles in the city of Plovdiv, Bulgaria - Mollov, Ivelin A. (Cambridge Scholars Publishing, 2019)
This book summarizes all available knowledge about the species composition and spatial distribution of amphibians and reptiles in the city of Plovdiv, in South Bulgaria. It also traces the dynamics of their populations and communities, along the urban-to-rural gradient, in order to determine their frequency of occurrence in time and the Important Herpetological Areas in the city. The book also provides additional ecological, zoogeographical and conservational data to further its points. It is the first comprehensive study on the urban ecology of amphibians and reptiles in the city of Plovdiv.